Smoking among adolescents in Jordan: Prevalence, associated factors, and its relation to mental health outcomes - Sara Abu Khudair; Yousef Khader; Mohannad Al Nsour; Eizaburo Tanaka (PLoS ONE, 2026)
Purpose This study aimed to explore the prevalence of various forms of smoking among adolescents in Jordan, identify associated factors, and examine their relationships with mental and psychosocial problems. Methods Data were obtained from a large-scale, nationally representative, school-based survey conducted between December 2022 and April 2023 among children and adolescents aged 8–18 years in both host and refugee populations in Jordan. A multi-stage stratified cluster sampling design was employed to ensure national representativeness. The study utilized internationally recognized and validated tools that assessed several mental and psychosocial problems. The present analysis was restricted to adolescents only. Results Among the 4,407 adolescents included in the study, the most prevalent form of tobacco use was waterpipe (shisha) at 19.2%, followed by e-cigarettes (15.1%) and cigarettes (9.8%). In multivariate analysis, smoking odds increased significantly with age. Notably, compared with 12-year-olds, adolescents aged 18 had significantly higher odds of smoking cigarettes or waterpipe (OR = 5.9, 95% CI 3.8–9.2) and using e-cigarettes (OR = 4.5, 95% CI 2.7–7.4). Adolescents whose mothers had less than a diploma had lower odds of e-cigarette use (OR = 0.8, 95% CI 0.6–0.9). Compared with adolescents in central Jordan, those in the northern region had significantly lower odds of both cigarette/waterpipe use (OR = 0.8, 95% CI 0.6–0.9) and e-cigarette use (OR = 0.7, 95% CI 0.6–0.9). Palestinian camp refugees were significantly less likely than Jordanians to smoke cigarettes or waterpipe (OR = 0.4, 95% CI 0.2–0.9) but did not differ significantly in e-cigarette use. Smoking cigarettes or waterpipe was significantly associated with higher levels of several mental and psychosocial problems symptoms, including separation anxiety, emotional and behavioral difficulties (emotional symptoms, conduct problems, hyperactivity, relationship problems with peers, lower sociability, general behavioral difficulties), and PTSD, along with a higher risk of problematic Internet use. Also, smoking cigarettes or waterpipe was significantly associated with poorer quality of life across all dimensions (overall, physical health, psychosocial health, emotional functioning, social functioning, and school functioning). Adolescents who reported using e-cigarettes had significantly higher conduct problems, hyperactivity symptoms, and total difficulties scores, as well as lower prosocial behavior and poorer school functioning. Conclusion Adolescent smoking in Jordan remains a pressing public health issue, with waterpipe use emerging as the most common form and increasing with age across different nationalities. Smoking, whether in the form of cigarettes, waterpipe, or e-cigarettes, was associated with increased vulnerability to a range of mental health issues and diminished health-related quality of life. Addressing this issue requires a multifaceted and evidence-based approach, including developing school-based prevention and control programs, incorporating social competence and social influence curricula, enforcing existing tobacco laws, and introducing updated regulations in response to emerging trends and evidence, particularly targeting flavored products. Furthermore, prevention and control strategies need to implement targeted interventions that address both the psychosocial roots of smoking and its consequences.